Noncanonical imprinting: intergenerational epigenetic inheritance mediated by Polycomb complexes. (February 2023) - Inoue, Azusa
Abstract : Genomic imprinting is illustrative of intergenerational epigenetic inheritance. The passage of parental genomes into the embryo is accompanied by epigenetic modifications, resulting in imprinted monoallelic gene expression in mammals. Some imprinted genes are regulated by maternal inheritance of H3K27me3, which is termed noncanonical imprinting. Noncanonical imprinting is established by Polycomb repressive complexes during oogenesis and maintained in preimplantation embryos and extraembryonic tissues, including the placenta. Recent studies of noncanonical imprinting have contributed to our understanding of chromatin regulation in oocytes and early embryos, imprinted X-chromosome inactivation, secondary differentially DNA-methylated regions, and the anomalies of cloned mice. Here, I summarize the current knowledge of noncanonical imprinting and remark on analogous mechanisms in invertebrates and plants.